The 8th European Conference on Antennas and Propagation (EuCAP 2014) 2014
DOI: 10.1109/eucap.2014.6902553
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven inversion of GPR surface reflection data for lossless layered media

Abstract: Abstract-Two wavefields can be retrieved from the measured reflection response at the surface. One is the Green's function at a chosen virtual receiver depth level in a layered model generated by a source at the surface. The other wavefield consists of the upgoing and downgoing parts of a wavefield that focuses at the virtual receiver depth level. From the upgoing part of the focusing wavefield an image can be computed at one-way vertical travel time and with correct amplitudes of the local reflection coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…It is a full waveform inversion method if the electric and magnetic parameters are obtained as a function of the subsurface position. Recently, some datadriven methods based on the Marchenko scheme have been proposed [11,15,17]. It was shown that the wave fields and focusing wave fields inside an unknown medium can be retrieved by solving a set of Marchenko-type equations [11,19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is a full waveform inversion method if the electric and magnetic parameters are obtained as a function of the subsurface position. Recently, some datadriven methods based on the Marchenko scheme have been proposed [11,15,17]. It was shown that the wave fields and focusing wave fields inside an unknown medium can be retrieved by solving a set of Marchenko-type equations [11,19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some datadriven methods based on the Marchenko scheme have been proposed [11,15,17]. It was shown that the wave fields and focusing wave fields inside an unknown medium can be retrieved by solving a set of Marchenko-type equations [11,19]. The Marchenko inversion scheme can be implemented as long as the Green's function or/and the focusing function are obtained because the local reflectivity or impedance can be obtained as a starting point for further inversion [11,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be used to eliminate the effect of internal multiples in a seismic or GPR image [9][10] [11]. A GPR inversion method for lossless medium based on Marchenko method has been developed [12]. This is a data-driven method, but it can deal only with lossless media and still needs to know the source signature.…”
Section: Introductionmentioning
confidence: 99%